2013
DOI: 10.1111/cch.12097
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ experiences with physical and occupational therapy for their young child with cerebral palsy: a mixed studies review

Abstract: Understanding the experiences of parents with their child's intervention might help meet the needs of parents and, subsequently get them engaged in their child's intervention. As parents' early beliefs regarding their child's intervention has consequences for treatment participation, it is important to understand these parental perspectives. The aim of this mixed studies review was to give an overview of the experiences and related factors of parents of young children (0-5 years of age) with cerebral palsy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 29 publications
2
69
0
10
Order By: Relevance
“…The themes reported by our study are also similar to those suggested in studies of families' experiences of other paediatric rehabilitation services and interventions—that while families' experiences are both individual (Nijhuis et al, ) and change over time (Piggot, Paterson, & Hocking, ), families value being included as part of their child's care team and being empowered to make decisions regarding their child's treatment (Kruijsen‐Terpstra et al, ), communication between agencies (Peplow & Carpenter, ), having access to a network of people with similar experiences (Knis‐Matthews et al, ), and acknowledgement of their broader circumstances (Kruijsen‐Terpstra et al, ). Priorities for service improvement activities to move towards greater family‐centred services should therefore focus on these areas (see Box ).…”
Section: Discussionsupporting
confidence: 79%
“…The themes reported by our study are also similar to those suggested in studies of families' experiences of other paediatric rehabilitation services and interventions—that while families' experiences are both individual (Nijhuis et al, ) and change over time (Piggot, Paterson, & Hocking, ), families value being included as part of their child's care team and being empowered to make decisions regarding their child's treatment (Kruijsen‐Terpstra et al, ), communication between agencies (Peplow & Carpenter, ), having access to a network of people with similar experiences (Knis‐Matthews et al, ), and acknowledgement of their broader circumstances (Kruijsen‐Terpstra et al, ). Priorities for service improvement activities to move towards greater family‐centred services should therefore focus on these areas (see Box ).…”
Section: Discussionsupporting
confidence: 79%
“…[6,7] It is widely recognized that parents and families play a crucial role in a child's life and participation in rehabilitation programs. [8] The cognitive orientation to daily occupational performance (CO-OP) is a client-centered, goalfocused, task-specific training approach that combines motor learning with cognitive problem-solving strategies.…”
Section: Introductionmentioning
confidence: 99%
“…[6,8] Children are reliant on the involvement of their families in order to access services, and receive an adequate dose of therapy. Given the critical role that parents play, it is important to consider the parent's lived experience of undertaking therapeutic treatments with their child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health education thus becomes a vital component of early intervention; based on a familycentered approach or practice, providing mechanisms and strategies for family empowerment, intensity and continuity of care, promoting better family adaptation to children with disabilities, lower levels of stress, anxiety and family frustration 3 ; In addition to providing children with many and better opportunities for active practice within their daily routines 4 . It is understood today that the health team must be able to understand the experiences and guide the parents and/or caregivers of children with disabilities; to listen to them and to recognize them as part of a joint strategy of coping and comprehensive rehabilitation of these children 5 . Avoiding harmful attitudes, such as passivity, where parents and families become mere replicators of what is oriented to them, without the actual knowledge of the condition of their children and/or the purpose of the guidelines.…”
mentioning
confidence: 99%